Respon Petani Terhadap Penggunaan Pupuk Organik di Desa Punggul, Kecamatan Abiansemal, Kabupaten Badung - I Ketut Arnawa; Nyoman Utari Vipriyanti; Ida Ayu Made Dwi Susanti; Godelifa Sarina Densi (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
Farmers' response to the use of organic fertilizers in Punggul Village, Abiansemal District, Badung Regency. This study aims to determine the response of farmers to the use of organic fertilizers in Punggul Village, Abiansemal District, Badung Regency. The research was conducted in August 2022 - February 2023. Farmers' responses to the use of organic fertilizers in Punggul Village, Abiansemal District, Badung Regency. Methods of data collection in the form of interviews, questionnaires, and documentation. Data analysis in this study used descriptive qualitative analysis which was analyzed using a Likers scale. The response of farmers to the use of organic fertilizers in Punggul Village, Abiansemal District, Badung Regency was very responsive 23 people with a percentage of 76.6% and sufficient response of 7 people with a percentage of 23.3% Based on the distribution of farmers according to their response to the use of organic fertilizers in Punggul Village, Abiansemal subdistrict, Badung regency. the answers obtained are included in the good category